THE EFFECT OF ORGANIZATIONAL CULTURE, MOTIVATION AND TRAINING ON EMPLOYEE PERFORMANCE AT THE REGIONAL DEVELOPMENT PLANNING BOARD OF WEST JAVA PROVINCE - Eko Santoso, Wiharso; Moeins, Anoesyirwan (Dinasti Publisher, 2019)
The performance of members of an organization is needed to support organizational performance. The performance of employees at the DKI Jakarta Provincial Development Planning Agency will affect the performance of these government agencies. The purpose of this study is to find out how much the role of organizational culture, motivation, and training in order to improve the performance of employees in the Regional Development Planning Agency of DKI Jakarta Province, both simultaneously and partially. The method used in this research is descriptive and verification method. The source of the data in this study were employees of the DKI Jakarta Provincial Planning Agency. Primary data was collected by way of questionnaires and interviews with employees BAPPEDA Jakarta. Secondary data was collected by means searches the documents that are relevant to the problem under study. The results of descriptive data analysis on the research variables indicate that organizational culture, motivation, training, and employee performance in the DKI Jakarta BAPPEDA are in the good category. Organizational culture, motivation, and training have a significant role in order to improve employee performance , which is equal to 72.2%. Variable motivation has a role more dominant in order to improve the performance of employees of Bappeda Province of Jakarta as having beta value most 37.1%.